Assessing Science-Based Solutions to Forest Management: A Case Study of the Upper Brantas River in Indonesia - Dharmawan, Budi; Sukmawati, Musdzalifah; Bala, Imam Ade; Muttaqin, Tatag (Technium Social Sciences Journal, 2023)
Brantas river spring area (KMASB) is located in Batu, East Java, Indonesia. The forest areas nowadays are damaged because its function is changing from forest to agriculture. Efforts to solve these problems require the involvement of various parties. Including scientific solutions to provide input in policy formulation. The transfer of scientific knowledge in policy can work depending on whether decision-makers can turn scientific advice into policies that are acceptable to all actors involved. To investigate the procedure for sharing scientific knowledge from cases of endangered Brantas River resources in Indonesia, we adopt the "research-integration-utilization" model of science-policy interaction. Scientific knowledge is created through scientific systems (research). Political actors implement a scientific-based solution to answer the problems (utilization), and there must be significant linkages between research and utilization (integration). We use empirical data to evaluate hypotheses about the research-integration-utilization model based on document analysis and expert interviews. According to our research, the local government’s use of its limited authority and improper application of scientific findings are to blame for the failure of knowledge transfer. The Batu city government cannot turn the scientific solution into a regulation while being required to employ scientifically sound solutions as a prerequisite for creating regional regulations. The Batu city government put its own solutions into practice because they think they are comprehend more thoroughly than the researchers. Researchers are unable to participate in the integration process since the Batu city government is a powerful actor to determine the scientific suggestions that are made